Atmospheric pressure dielectric barrier discharge involving ion-induced secondary electron emission controlled by dielectric surface charges. (23rd August 2019) - Yao, Congwei; Chen, Sile; Chang, Zhengshi; Mu, Hai-Bao; Zhang, Guan-Jun
Abstract: Secondary electron emission (SEE) induced by interaction between positive ion and dielectric surface is essential physical process for maintaining sustained discharge and controlling the characteristics of atmospheric pressure dielectric barrier discharge (DBD). In this work, SEE is described based on Auger neutralization theory. Dielectric energy band structure and defect energy level, including hole and electron trap energy levels, are taken into account to build a hypothetical relationship γ i = f ( σ ) between secondary electron emission coefficient γ i and surface charge density σ . With the introduction of γ i = f ( σ ) in DBD model, the characteristics of DBD are discussed in both first and steady discharges. It is found that, in steady discharge, γ i has higher value during the beginning and development state of discharge pulse of DBD, and γ i decreases in extinction stage. The negatively charged dielectric surface enhances SEE before discharge, which benefits the formation of diffuse discharge, compared with DBD of constant γ i . Moreover, the increase of energy band gap of dielectric reduces γ i, leading to the contractive discharge in DBD. The relationship between γ i and σ can be further applied to study the influences of defect energy level parameters on SEE and DBD characteristics.